Clinical Efficacy of Real-Time Sonoelastography for the Follow-Up of Congenital Sternocleidomastoid Muscle Torticollis - Jeong, Mi ri; Lee, In Sook; Shin, Yong Beom; Song, You Seon; Park, Sekyoung; Song, Jong Woon; Moon, Jin Il (Journal of the Korean Society of Radiology, 2020)
Purpose To evaluate the clinical efficacy of real-time sonoelastography (RTS) for the follow-up of congenital muscular torticollis, based on measurements of muscle elasticity. Materials and Methods Thirty-four infants (23 male, 11 female) with congenital sternocleidomastoid (SCM) muscle torticollis underwent ultrasonography and elastography between November 2012 and December 2014. We evaluated the thickness, morphology (mass-like, fusiform, or overall thickened shape), and echogenicity of the SCM muscle on grayscale images and color patterns (homogeneous blue, mixed green < 50% and ≥ 50%, and green to red) on elastography. Strain ratios were measured using Q-lab software. A clinician classified the degree of neck rotation and side flexion deficits using a 5-point grade system based on angles of neck rotation and side flexion. Correlations between the ultrasonography and clinical findings were evaluated by statistical analysis. Results Twenty-two infants had right and 12 had left SCM torticollis, respectively. Linear regression analysis showed that involved/contralateral SCM thickness differences, morphology, elasticity color scores, and strain ratios of the affected SCM muscles were significantly correlated with neck rotation and side flexion deficit scores (p < 0.05). The elasticity color score of the affected SCM muscle was the most significant factor. Conclusion RTS might provide a reliable means for evaluating and monitoring congenital muscular torticollis.